Adolescent-friendly technologies as potential adjuncts for health promotion. Issue 4 (2nd June 2014) - Dietrich, Janan J.; Coetzee, Jenny; Otwombe, Kennedy; Mdanda, Sanele; Nkala, Busisiwe; Makongoza, Matamela; Tshabalala, Celokhuhle; Hornschuh, Stefanie; Soon, Christine N.; Kaida, Angela; Hogg, Robert; Gray, Glenda E.; et al.
Abstract : Purpose: – The purpose of this paper is to measure prevalence and predictors of mobile phone access and use among adolescents in Soweto, South Africa. Design/methodology/approach: – The current study was an interviewer-administered, cross-sectional survey among adolescents 14-19 years living in a hyper-endemic human immunodeficiency virus (HIV) setting in South Africa. Findings: – Of 830 participants; 57 per cent were female. The median age was 18 years (IQR: 17-18). Mobile phone access was high (91 per cent). Almost half of participants (42 per cent) spent more than five hours daily using their mobile phones. Two-thirds (62 per cent) had access to the internet, most (84 per cent) accessed the internet via their mobile phones. Mobile phone access was more likely amongst Sotho language speakers (aOR: 2.87, 95 per cent CI: 1.30-6.36), those living in formal housing (aOR: 3.55, 95 per cent CI: 1.97-6.42) and those who reported heterosexual orientation (aOR: 2.37, CI: 1.35-4.16). Originality/value: – This study substantially contributes to the literature about mobile phones usage and patterns among school-going adolescents in Soweto, South Africa.